GYNECOMASTIA IN CHILDREN AND YOUNG MEN - Олеся Викторовна Будникова; Юрий Иванович Ровда (The Publishing House Medicine and Enlightenment, 2021)
It is well known that mammary glands in boys and girls are identical before puberty. However mammary glands' enlargement is often recorded in male persons during puberty. This condition is not only a medical, but also a social problem. Athletics, equal peer relationships and communication with girls can be difficult or even impossible for boys with gynecomastia. Adolescents with such a problem also have a posture disorder in addition to psychological complexes and social maladjustment. For many years they slouch, trying to hide enlarged breasts, which leads to a curvature of the spine. Usually parents of such children go to a pediatrician and get advice to wait indefinitely. There fore the presented literature review analyzes modern data on the etiology, pathogenesis, clinic and diagnosis of breast enlargement for timely assistance to such adolescents.